2020
DOI: 10.5812/jjcdc.104260
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Epidemic and Spirituality: A Review of the Benefits of Religion in Times of Crisis

Abstract: Context: The current world crisis, COVID-19 disease, is different from any other world’s previous crises since it has killed thousands of people all around the world and made the medical science desperate. During the COVID-19 outbreak, spirituality can be one of the proper methods to create mental relaxation. Evidence Acquisition: The present study is a review of the literature from 1978 to 2019. The search was done in electronic databases and reputable websites including PubMed, Medline, Springer, Els… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 28 publications
1
47
0
8
Order By: Relevance
“…In this connection, Muslims can pray and perform religious rituals to ask God to heal the suffering and the patients. It will contribute to the support of the people as a whole [46].…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, Muslims can pray and perform religious rituals to ask God to heal the suffering and the patients. It will contribute to the support of the people as a whole [46].…”
Section: Discussionmentioning
confidence: 99%
“…The final impact of the COVID-19 pandemic is still unclear; however, its psychological effects are certain, including worry about getting infected, fear of death, disappointment, job burnout, and negative emotions, all of which affect the physical and emotional health of society (16). Additionally, depression, PTSD, insomnia, anxiety, anger, and even suicide in patients and their families are other psychological consequences of the COVID-19 prevalence (25). In Italy, research showed a high percentage of PTSD symptoms during the COVID-19 pandemic in the community, which resulted in sleep problems (26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, psychologists and psychi- atrists should look for novel techniques to decrease the impacts of the COVID-19 outbreak. As an instance, during this global crisis, spirituality is useful for staying calm (25). As a result, it can be argued that the COVID-19 outbreak has influenced important aspects of our lives, particularly through negative emotions, so mental health teams should be formed to improve the general public's emotions by providing online or in-person psychological services with complete and updated treatment information and programs.…”
Section: Discussionmentioning
confidence: 99%
“…Max Regus (2021) menegaskan bahwa agama memiliki dua sisi yang bertolak belakang dalam kaitannya dengan COVID-19. Pada satu sisi, agama memiliki aturan yang potensial untuk mengurangi atau bahkan menghentikan pandemi ini (Barmania & Reiss, 2020;Everett, Colombatto, Chituc, Brady, & Crockett, 2020;Fardin, 2020), tetapi di sisi lain agama juga dapat menjadi medium penyebaran Covid-19 Ebrahim, Ahmed, Gozzer, Schlagenhauf, & Memish, 2020). Rutinitas Muslim yang setiap Jumat wajib menunaikan salat jamaah Jumat, misalnya, berubah dan lebih banyak dilakukan di rumah dan beribadah secara mandiri/munfarid (Ghofur & Subahri, 2020;Siregar & Jubba, 2020) dalam rangka menghindari penyebaran COVID-19.…”
Section: Pendahuluanunclassified